ANALISIS PERKEMBANGAN RETRIBUSI PASAR DAERAH SEBAGAI SUMBER PEMBIAYAAN OTONOMI DAERAH DI KABUPATEN PEMALANG TAHUN 2007-2011 - Asep Tri Handoko (Economics Development Analysis Journal, 2012)
This research is a type of research descriptions on Diskoperindag and DPPKAD PemalangDistrict with the title “Analysis of Growth Regional Market Retribution and contribution to regional outonomy expensed from 2007 to 2011”. The purpose of this study was to analyze the development market retribution to areas adopted duringthe Pemalang District by referring to the Act. 28 of 2009 and Local Regulation No. 14 of 2007 on Market retribution. The stages of analysis used by the author in the study were: (1) identify the growth market acceptance retribution. (2) effectivenessanalysis. (3) effisieness analysis (4) growth analysis. (5) analysis contribution. Results of research on distric Pemalang show. (1) the growth of market acceptance of user charges in district Pemalang been quite effective, reach out for and touch effisienand experience fluctuation growth. (2) retribution contribution to outonomy regional income (PAD) from 2007 to 2011 has quite low/small. The conclusion of this research is the growthand contribution of market acceptance in Pemalang district guite low and need to increase..